Shopgirl - Martin, Steve, 1945- (New York : Simon & Schuster Audio, 2000)
Slightly lost, slightly off-kilter, very shy, Mirabelle captures the attention of Ray Porter, a wealthy businessman almost twice her age. As they tentatively embark on a relationship, they both struggle to decipher the language of love.
An unabridged recording of the book read by the author.
In container (17 cm.).
Keywords: Clerks (Retail trade) -- Fiction; Department stores -- Fiction; Medication abuse -- Fiction; Young women -- Fiction; Beverly Hills (Calif.) -- Fiction; Humorous fiction; Bildungsromans; Audiobooks